Correlación entre: razón presión parcial de oxígeno en sangre arterial/fracción inspirada oxígeno y razón saturación periférica de oxígeno/fracción inspirada de oxígeno en pacientes con choque y/o acidosis metabólica tratados con vasopresores. Perú-2014 - Morales Nureña, Ramón Rodolfo (2017)
With the aim of determining if a correlation exists between the ratios Arterial oxygen partial pressure/Oxygen inspired fraction (PaO2/FiO2) and Oxygen Peripheral Saturation/Oxygen inspired fraction (SpO2/FiO2) in a heterogeneous set of severe low-perfusion critically ill patients, arterial blood gases data were obtained from 36 metabolic acidosis and/or shock patients (vasopressors-treated) admitted to Unidad de Vigilancia Intensiva at Hospital II EsSalud Chocope, 2014. The Pearson´s correlation coefficient was 0.9357 (Confidence interval 95%: 0.8766 – 0.96696) p=0.0001. The correlation between PaO2/FiO2 and SpO2/FiO2 was very strong. The study also showed SpO2/FiO2 had exceptional ability to discrimiminate between PaO2/FiO2 ´s different cut-off points.